Analysis of X and Threads Responses Based on Single Keywords Using Graph Neural Network - Sinaga, Rifky Fahriza; Rizal, Rizal; Anshari, Said Fadlan (Mulawarman University, 2026)
This study analyzes user responses on the social media platforms X and Threads regarding radicalism, based on the single keyword